Sosialisasi Sadar Akan Aktivitas Fisik Secara Rutin Guna Terhindar Dari Penyakit Tidak Menular Di Desa Lamglumpang Aceh Besar - Yadi Putra; Fauziah Fauziah; Yunita Yani; Jahra Salsabila; Zarra Zattira; Vina Rahmatina (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Non-communicable diseases (NCDs) are chronic diseases that cannot be transmitted from person to person. Deaths from NCDs are expected to continue to rise worldwide, with the greatest increase occurring in developing and poor countries. Non-communicable diseases (NCDs) cause the death of approximately 35 million people each year. Non-communicable diseases can be prevented by doing regular physical activity. The purpose of community service activities is to increase public understanding of routine physical activity to avoid non-communicable diseases. The activity was carried out on Thursday, January 18, 2024 for 60 minutes. Participants in community activities are mothers. The activity was held at the Lamglumpang village mosque. The implementation of this activity with the opening of the event by the village head, introductions, distribution of pre-test questionnaires, provision of material for 30 minutes followed by a question and answer discussion and distribution of post-test questionnaires. The results of the pre-test and post-test showed an increase in community understanding of physical activity against non-communicable diseases. Understanding of physical activity pres-test amounted to 1.40% and post-test understanding amounted to 1.53%. understanding of physical activity increased after being given socialization to the community.